2001
DOI: 10.1016/s0927-7757(01)00545-3
|View full text |Cite
|
Sign up to set email alerts
|

Swelling and dissolution of onion phases: the effect of temperature

Abstract: Contact experiments have been performed between an onion lamellar phase and brine, in the SDS/octanol/brine system. Using video microscopy we have studied the nonequilibrium behaviour of the swelling and dissolution process of onions. Experiments at T = 20 • C and 30 • C showed that temperature has a strong effect on their behaviour. At low temperature onions are observed to diffuse away from the onion phase and only swell sightly. However by increasing the temperature we induce the formation of sponge phase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These interface instabilities can form during the dissolution and swelling of surfactant lamellar phases. Despite an increasing interest in these structures, there is currently no accepted explanation for the formation of myelins.…”
Section: Introductionmentioning
confidence: 99%
“…These interface instabilities can form during the dissolution and swelling of surfactant lamellar phases. Despite an increasing interest in these structures, there is currently no accepted explanation for the formation of myelins.…”
Section: Introductionmentioning
confidence: 99%
“…As the increase of temperature led to poor retention of soaps and phospholipids, we assume that this can be the result of increasing solubilisation of soaps and phospholipids as monomers or/and small clusters in the continuous triglyceridic phase and/or of a change of the structures of the aggregates. In fact, Buchanan, Egelhaaf, and Cates (2001) reported that at 30 8C onion phases can dmeltT into a sponge phase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the presence of silica particles causes extensive coiling of myelin structures. Due to the strong concentration gradients, the interface between pure surfactant and pure water can consist of multiple domains of different phases, as well as metastable structures whose origins are not understood, evolving in spatially and temporally complex ways [8][9][10][11]. Huang et al showed that even a slight increase in the overall hydration can overcome the added elastic energy of forming a myelin.…”
Section: Introductionmentioning
confidence: 99%